MISSIONARIES INVOLVEMENT IN AFRICA DURING THE 19TH CENTURY - Fathi, Amina (My University, 2020)
Missionaries came to Africa under the concept of civilization; they considered Africans savage and inferior to whites. Missionaries came to spread Christianity in the beginning, but they had hidden intentions, they worked to pave the way for European colonialism. Missionaries such as David Livingstone were sent by the London Missionary Society in 1840 to Africa, they worked to convert the inhabitants to the new faith where they were initially refused, but later these missionaries were able to convince the Africans accept Christianity gently. Missionaries built clinics to treat sick people and created schools to teach children English and the new doctrine, these pages became interpreters that made it easy for missionaries to contact and control African leaders. quickly. Africa was a mystery to Europeans and they only discovered it in the 19th century due to many difficulties. The black continent was in great demand by Europeans because it was rich in natural resources and minerals, Europeans saw it as a solution to all their economic and social problems.
Keywords: Africa; Missionaries; David Livingstone; London Missionary Society; Christianity; European colonialism